CAN GOOD GOVERNANCE ENHANCE LOCAL GOVERNMENT PERFORMANCE? - Rafrini Amyulianthy; Ruhaini Muda; Jamaliah Said; Dyah Setyaningrum; Harnovinsah Harnovinsah (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2023)
The first objective of this study is to examine the effect of audit results on the local government performance. Secondly is examining the moderating role of good governance on the relationship between audit results and local government performance. This study collected 536 local governments data from 134 local authorities in Indonesia from 2016 to 2019. The data employed for audit results were extracted from findings and rectification of audit reports. For the Good Governance, this study develops the Good Governance Principles index by mapping the data taken from Evaluation of Local Government Performance by the Ministry of Home Affairs RI with IGI indicators. Meanwhile, the local government performances were measured using the total local own revenue. This study uses multiple moderated regression analyses to explain the relationship between the audit results and good governance on local government performance. As the result, it has a significant effect on both variables tested. This research also found a significant interaction between audit results and good governance on local government. These results assert that good governance enhances local government to be more effective in responding to audit results to improve their performances in the following years.